EFFECT OF 6 WEEKS OF CIRCUIT TRAINING ON INCREASED VO2 MAX - Moch Yunus (Jurnal Health Sains, 2023)
This study aimed to analyze the effect of 6 weeks of Circuit Exercise on increasing VO2max. The research design applied to this study used pre-experimental with one group pretest and posttest design. The number of subjects of this study was 24 Opel Futsal Club U-16 athletes in Lamongan Regency. The treatment in the study was in the form of circuit training, carried out as many as 18 meetings for 6 weeks with a frequency of exercise 3 times a week. The test instrument used in this study was a multistage fitness test. Technical analysis uses a t-test with the prerequisites of a normality test. The results of the study found that the VO2max mean pretest value was 39.29 ml / kg / minute and for the posttest mean results was 43.93 ml / kg / minute. The results of paired sample t-test analysis are 0.000 < 0.05. Based on the results of the analysis, it can be concluded that 6 weeks of circuit training can increase VO2max significantly.